PENGARUH MEDIA SMART ADVENTURE BOX TERHADAP LITERASI AWAL DI TAMAN KANAK-KANAK ISLAM MENTARI BUNDA - Tirsa Nur Adelin; Vivi Anggraini; Yulsyofriend; Indra Yeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low early literacy skills of children at Mentari Bunda Islamic Kindergarten, which is indicated by the large number of children aged 5-6 years who have difficulty recognizing letters, distinguishing similar letter shapes, and composing simple words, while learning is still dominated by conventional media such as letter cards and worksheets. A quantitative approach with a quasi-experimental pretest-posttest control group design was used, involving 30 children divided into an experimental class (n=15) using Smart Adventure Box and a control class (n=15) using flashcards and worksheets. Data were collected through observation using a validated five-indicator instrument and analyzed with an Independent Sample t-test after normality and homogeneity assumptions were met. Results showed the experimental class's total score increased from 169 (pretest) to 265 (posttest), higher than the control class's increase from 141 to 212, with a significant difference between groups (Sig. 2-tailed = 0.001 < 0.05). These findings indicate that Smart Adventure Box significantly improves early literacy skills and can be recommended as an interactive alternative learning medium for early childhood education.